Evaluation of yield and aphid resistance of Indian mustard (Brassica juncea) accessions under acidic soil of Meghalaya - TINGNUNNIANG; M JAMES; FARZANA AHMAD; RASHMI YADAV; HOSSAIN ALI MONDAL (The Indian Journal of Agricultural Sciences, 2024)
The present study was carried out during winter (rabi) season of 2021 at the Research Farm of College of Post Graduate Studies in Agricultural Sciences (Central Agricultural University, Imphal, Manipur), Umiam, Meghalaya to assess the yield and aphid resistance of Indian mustard accessions under acidic soil of Meghalaya. A total of 95 accessions were evaluated in the acidic soils of north-eastern hill regions (NEHR) of India with concomitant problems of low phosphorus availability and aluminum toxicity followed by a specialist and a generalist aphid resistance evaluation. The result evidenced that the number of siliques/plant (NSQPP), biological yield (BY), dry weight (DW), number of seeds/siliqua (NSPS), and number of secondary branches/plant (NSB) were found to be highly correlated with seed yield/plant (SYPP). Principal component analysis (PCA) gave a biplot with atleast two diverse groups. The extreme genotypes i.e. Vardan, RH-0923, RL-JEB-84, and PM24 of the first quadrant in PCA had high yield and its attributing traits. Aphid resistance study using different indices in the selected genotypes evidenced an elevated resistance level. The genotypes RMM-09-10 and RL-JEB-84 could be considered as higher resistant against both two aphid spp., Lipaphis erysimi and Myzus persicae, a specialist and generalist aphid, respectively.